Syndrome of Inappropriate Antidiuretic Hormone Secretion (SIADH): Optimal Management - Mentrasti G (Dove Medical Press, 2020)
Giulia Mentrasti,* Laura Scortichini,* Mariangela Torniai, Riccardo Giampieri, Francesca Morgese, Silvia Rinaldi, Rossana Berardi Clinica Oncologica, Università Politecnica delle Marche, AOU Ospedali Riuniti Di Ancona, Ancona, Italy*These authors contributed equally to this workCorrespondence: Rossana BerardiClinica Oncologica, Università Politecnica delle Marche, AOU Ospedali Riuniti Di Ancona, Via Conca 71, Ancona 60126, ItalyTel +39 071 5965715Fax +39 071 5965053Email r.berardi@univpm.itAbstract: Hyponatremia, defined as serum sodium concentration < 135 mEq/l, is the most common electrolyte balance disorder in clinical practice. Many causes are listed, but syndrome of inappropriate antidiuretic hormone secretion (SIADH) is certainly the most relevant, mainly in oncological and hospitalized patients. In this review, the pathophysiological and clinical aspects are described in detail. Patients’ extensive medical history and structured physical and biochemical tests are considered the milestones marking the way of the SIADH management as to provide early detection and proper correction. We focused our attention on the poor prognostic role and negative effect on patient’s quality of life of SIADH-induced hyponatremia in both malignant and non-malignant settings, stressing how optimal management of this electrolyte imbalance can result in improved outcomes and lower health costs.Keywords: SIADH, hyponatremia, prognosis, neoplasms, lung cancer